PENGARUH MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS - Winda Riana; Rini Rita T. Marpaung; Berti Yolida (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2015)
The aim of this research was to find out the influence of discovery learning model toward students critical thinking ability. The research design was pretest-posttest non equivalent. The samples of this research were the students of class VIID and VIIA SMP Kartika II-2 Bandar Lampung who were chosen by using purposive sampling. The quantitative data were obtained from the average score of pretest, posttest and N-gain which was tested by using T-test and U-test. The qualitative data were the students learning activities which were analyzed by descriptive analysis had an increase viewed from the average of N-gain of experiment class was 57,08. It is significantly different from control class was 25,33. The average of increase of students activity from the indicator of giving a simple explanation, building the basic creativity, giving further explanation and concluding had high criteria. It could be assumed that the learning using discovery learning model has an influence in increasing students critical thinking ability in the basic competence of the characteristic living creature.Penelitian ini bertujuan untuk mengetahui pengaruh discovery learning terhadap kemampuan berpikir kritis. Desain penelitian adalah pretest-posttest tak ekuivalen. Sampel penelitian adalah siswa kelas VIID dan VIIA SMP Kartika II-2 Bandar Lampung yang dipilih secara purposive sampling. Data kuantitatif berupa rata-rata nilai pretest, posttest dan N-gain yang di uji menggunakan uji-t dan uji U. Data kualitatif berupa aktivitas belajar siswa yang dianalisis secara deskriptif. Hasil penelitian menunjukkan kemampuan berpikir kritis siswa mengalami peningkatan dilihat dari rata-rata N-gain kelas eksperimen sebesar (57,08) berbeda signifikan dengan kelas kontrol (25,33). Rata-rata peningkatan aktivitas siswa pada indikator memberikan penjelasan sederhana, membangun keterampilan dasar, memberikan penjelasan lanjut dan menyimpulkan berkriteria tinggi. Dengan demikian, pembelajaran menggunakan model discovery learning berpengaruh dalam meningkatkan kemampuan berpikir kritis pada materi pokok ciri-ciri makhluk hidup.Kata kunci: berpikir kritis, discovery learning, pengaruh